Fertilizer subsidies in Malawi: From past to present - Benson, Todd; De Weerdt, Joachim; Duchoslav, Jan; Masanjala, Winford (International Food Policy Research Institute, 2024)
Malawi has been at the center of the debate on agricultural input subsidies in Africa ever since it significantly expanded its fertilizer subsidy program about two decades ago. When it did so, Malawi was a trailblazer, receiving international attention for seemingly leveraging the subsidy program to move the country from a situation characterized by food deficits and widespread hunger to crop production surpluses. In this paper we trace the history of Malawi’s subsidy program over the past 70 years, describing how the country arrived at that watershed moment earlier this century and how the subsidy program has developed since. We show how donor support for the program has wavered and how external pressure to remove the subsidy has repeatedly been unsuccessful. We also demonstrate how over the years the program’s total fiscal burden has fluctuated significantly. However, we find that since the expansion of the subsidy program in 2004, the fiscal costs of the program have shown little correlation with the maize harvest that same agricultural season. We show that the subsidy program has succeeded in raising awareness about the value of the fertilizer for increased crop productivity. However, despite its continued prominence in the country’s agricultural policy, most Malawian smallholder do not manage to grow sufficient maize to feed their households throughout the year, and every year millions depend on food assistance during the worst months of the lean season.